Nursing Perspectives: Reflecting History and Informal Coercion in De-escalation Strategies - Rabenschlag, Franziska; Cassidy, Christoph; Steinauer, Regine (Frontiers in Psychiatry, 2019)
Health professionals like nurses respond to aggression and violence with de-escalation techniques, and still often with coercive measures. The type of those measures used by institutions can have historically grown traditions rather than evidence, reflection or formation. De-escalation strategies in the mental health practice should be based on a high and critical awareness towards the practice of formal and informal coercion and is an ongoing intersubjective process.